Prophetic Leadership in the Development of Religious Culture in Modern Islamic Boarding Schools - Umar Sidiq; Qurrotul ‘Uyun (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
Prophetic leadership is prophetic leadership. The main aim of the prophetic task is to teach humans how to get happiness and safety, both in this world and the hereafter. This study is to describe and analyze 1) Prophetic leadership strategies in the development of religious culture in Boarding school Modern Arrisalah Gundik Slahung Ponorogo, East Java, Indonesia. 2) Supporting and inhibiting factors in the application of prophetic leadership in Boarding school Gundik Slahung Ponorogo, East Java, Indonesia. 3) The results of the implementation of prophetic leadership in the development of religious culture at Boarding school Modern Arrisalah Gundik Slahung Ponorogo, East Java, Indonesia. The concept of prophetic leadership that is understood by the leaders of Boarding school Modern Arrisalah is simply by imitating the Prophet Muhammad. Following the capacity of humanity. Generally, prophetic leadership is done by emulating four characteristics of the Prophet. He is honest in everything, including conveying his knowledge honestly, correctly and can be tested for its source. He mandated his leadership, did what he ordered for all the clerics and his students; he also never renounced his leadership. He tabligh, conveyed everything that he had so far for the benefit of the cleric and his students. He is intelligent in all aspects of behaviour and mind, so now he is the idol of the students.Kepemimpinan profetik adalah kepemimpinan yang bersifat kenabian. Tujuan utama dari tugas kenabian ialah untuk mengajarkan kepada manusia bagaimana cara mendapat kebahagiaan dan keselamatan, baik di dunia maupun akhirat. Kajian ini untuk mendeskripsikan dan menganalisis tentang 1) Strategi prophetic leadership dalam pengembangan budaya religius di Pesantren Modern Arrisalah Gundik Slahung Ponorogo, Jawa Timur, Indonesia. 2) Faktor pendukung dan penghambat dalam penerapan prophetic leaership di Pesantren Modern Gundik Slahung Ponorogo, East Java, Indonesia. 3) Hasil penerapan prophetic leadership dalam pengembangan budaya religius di Pesantren Modern Arrisalah Gundik Slahung Ponorogo, Jawa Timur, Indonesia. Konsep prophetic leadership yang dipahami oleh pimpinan Pesantren Modern Arrisalah secara sederhana ialah dengan meneladani Nabi Muhammad Saw. sesuai dengan kapasitas umat manusia. Umumnya prophetic leadership dilakukan dengan meneladani empat sifat Nabi. Beliau jujur dalam segala hal termasuk menyampaikan ilmu dengan jujur, benar dan bisa diuji sumbernya. Beliau amanah terhadap kepemimpinannya, melakukan apa yang beliau perintahkan untuk semua ustadz dan para santrinya, beliau juga tak pernah ingkar terhadap kepemimpinannya. Beliau tabligh, menyampaikan segala sesuatu yang beliau dapat selama ini untuk kemaslahatan ustadz dan para santri-santrinya. Beliau cerdas dalam segala aspek perilaku dan pikiran, sehingga sampai sejauh ini beliau adalah idola para santri.